Evaluation of the Experiences of Health Service Management Students at the Faculty of Management and Information in Tabriz, Iran Regarding Field Internship: A Qualitative Research - Ali Jannati; Fariba Dehgani Milag; MohammadReza Narimani; Masoumeh Gholizadeh; Neda Kabiri (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Recognition and elimination of weaknesses in the internship courses of health service management are essential to improving their quality and efficacy. The present study aimed to evaluate the viewpoints of health service management students toward the challenges in the design and implementation of internship courses at the Faculty of Management and Information in Tabriz University of Medical Sciences, Iran. Materials and Methods: This qualitative research was conducted on the health service management students at the Faculty of Management and Information in Tabriz University of Medical Sciences in 2014. Data were collected via focused group discussions attended by 8-10 individuals per session. Data analysis was performed using content analysis. Results: Challenges in internships 1-4 for bachelor's degree students were assessed in three areas, including the problems relating to instructors, internship courses, and cartable from the perspective of the students. In total, 8 main themes and 30 subthemes were extracted in each area. Conclusion: According to the results, the internship curricula of health service management students should be completely modified to eliminate the weaknesses. These changes must include the correction of the course design and syllabi and essential revision of the cartable based on the latest information on health systems and labor market needs.